Optic Pathway–Hypothalamic Glioma Apoplexy: A Report of Two Cases and Systematic Review of the Literature - Baeesa, Saleh; Maghrabi, Yazid; Moshref, Rana; Al-Maghrabi, Jaudah (Frontiers in Surgery, 2022)
Background: Hemorrhage into optic pathway-hypothalamic glioma (OPHG) is rare. Variable clinical presentations and outcomes are associated with such pathology. We aim to present two infants presented with OPHG and a systematic review of the literature Methods: We describe two cases of infants presenting a sudden decreased vision, poor feeding, and irritability due to OPHG. Both patients underwent urgent craniotomy and subtotal resection followed by chemotherapy. We systematically reviewed the literature using PubMed, Google Scholar, and Embase. In addition, we included all English published reports discussing optic pathway (optic nerve and optic chiasm) or hypothalamic glioma associated with hemorrhage from the year of the first reported case (1970) to January 2022. Results: Of 17949, 44 articles met the inclusion criteria of this review. Total 56 cases were described with a mean of 21.35 years (0.5-70), with the male gender 52% and the female gender 45%. The hemorrhage location was sellar/suprasellar in 43% of cases. Histopathology of included cases was pilocytic astrocytoma in 41%, followed by pilomyxoid astrocytoma in 16% of cases. The outcome was not favorable; 37.5% of cases showed improvement, whereas 18% of cases resulted in death. Conclusion: Apoplexy of the OPHG can be fatal and associated with poor outcomes. A systematic review of literature has shown that younger age, pilocytic or pilomexyoid astrocytoma histopathology, and chiasmal/hypothalamic locations are associated with a higher risk of intertumoral hemorrhage and poor prognosis.